Besides the Bible : 100 books that have, should, or will create Christian culture - Gibson, Dan; Green, Jordan; Pattison, John (Downers Grove, IL : InterVarsity Press, 2010)
This book is a guide to the really great books that you "should" read - ones that matter. Covering a wide array of subjects and authors, from Christian bookstore bestsellers to classics of Christian history and more, you'll find yourself agreeing with some titles, shaking your head at others, and even shocked by a few. This isn't a dry catalog with dull summaries of books authored by a bunch of dead guys. Dan Gibson, Jordan Green, and John Pattison, along with an outstanding team of some of today's most interesting Christian thinkers (including Donald Miller, Phyllis Tickle, Steve Taylor, and William P. Young) will reignite your love for reading, or if you're a little lazy, give you enough information to make it seem like you're incredibly well read. -- from back cover.
Description based on print version record.
Keywords: Christians -- Books and reading; Christians -- Books and reading -- Bibliography; Christianity and literature; Best books; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books